2007
DOI: 10.1021/jp0650937
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Surface Enhanced Raman Scattering Studies of 3-Hydroxyflavone on a Ag Electrode

Abstract: Reverse proton transfer (RPT) of 3-hydroxyflavone (3-HF) from the tautomer ground state to normal ground state has been studied by time-resolved surface enhanced Raman scattering (TRSERS) in aqueous solution in the presence of oxygen. The tautomer ground state of 3-HF is formed by an exciting 337 nm nitrogen laser pulse and monitored by a 488 nm Ar + laser with gated photodiode array detection. B3LYP DFT calculations with 3-HF bound to the apex adatom of a Ag 20 cluster model show that a tilted orientation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(101 reference statements)
0
16
0
Order By: Relevance
“…It has the power to provide excellent values for normal-mode vibrational frequencies and intensities. In recent studies, 3335 we have found that DFT software provides reliable and accurate ways of predicting and assigning the Raman bands of various dye molecules. Density functional theory has grown in popularity in computational chemistry because the calculations provide much better agreement with experimental values than the Hartree–Fock procedures.…”
Section: Introductionmentioning
confidence: 99%
“…It has the power to provide excellent values for normal-mode vibrational frequencies and intensities. In recent studies, 3335 we have found that DFT software provides reliable and accurate ways of predicting and assigning the Raman bands of various dye molecules. Density functional theory has grown in popularity in computational chemistry because the calculations provide much better agreement with experimental values than the Hartree–Fock procedures.…”
Section: Introductionmentioning
confidence: 99%
“…DFT has the power to provide excellent values for normal mode vibrational frequencies and intensities. In recent works (15–18), we have found that DFT gives reliable and accurate way to predict and therefore to assign the Raman bands of various dye molecules. DFT has grown in popularity in computational chemistry because the calculations provide much better agreement with experimental values than the Hartree–Fock procedures (19).…”
mentioning
confidence: 99%
“…The transition states and intermediates of the photooxidation of D were characterized with the help of potential energy surface (PES) calculations. A reaction path analogous to the experimentally established steps of the photooxidation of the parent compound, 3HF, [23][24][25][26][27] was considered. The results are illustrated in Fig.…”
Section: Reaction Mechanismmentioning
confidence: 99%